INTERACTIVE DISCUSSION ON ACCOUNTING AND HUMAN RESOURCE MANAGEMENT WITH SMES AT BANGKOK SHOPPING CENTERS - Wenni Wahyuandari; Lona Chinsia Alfattama (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tulungagung, 2026)
Small and Medium Enterprises (SMEs) play a vital role in economic growth and employment, particularly in Southeast Asia. Despite their significance, many SMEs face persistent challenges in implementing proper accounting practices and effective human resource management (HRM), which limit their business sustainability and competitiveness. This community service program aimed to address these challenges through an interactive discussion on accounting and HRM with SMEs operating in shopping centers in Bangkok, Thailand. The activity was conducted from 20–23 February 2025 and involved SME owners and managers as primary participants. Using a participatory and two-way discussion approach, the program introduced practical accounting techniques, such as simple financial recording and cash flow management, as well as basic HRM strategies related to employee motivation, retention, and work efficiency. The results of the activity indicate that most SMEs still rely on informal management practices but demonstrate strong motivation to improve when provided with practical and accessible knowledge. The interactive format facilitated effective knowledge exchange between academics and entrepreneurs and strengthened cross-cultural collaboration between Indonesian academics and Thai SMEs. Overall, the program contributed to enhancing SMEs’ understanding of accounting and HRM, supporting their long-term business sustainability, and reinforcing the role of universities in international community engagement and sustainable economic development.